2015
DOI: 10.17221/16/2015-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

The selection and validation of a marker set for the differentiation of onion cultivars from the Czech Republic

Abstract: Mitrová K., Svoboda P., Ovesná J. (2015): The selection and validation of a marker set for the differentiation of onion cultivars from the Czech Republic. Czech J. Genet. Plant Breed., 51: 62-67.The onion (Allium cepa L.) constitutes an important part of the human diet and is of economic importance on the vegetable market. Methods that allow unambiguous differentiation of cultivars and breeding lines are required for market control and the protection of plant breeders' rights. DNA analyses, such as single sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
4
16
0
Order By: Relevance
“…Molecular markers, namely SSR, are widely used in plant breeding as they are associated with certain traits (Collard & Mackill 2008). Presented data confirmed that a previously developed SSR marker set (Mitrová et al 2015) could be used not only for cultivar authentication but also as quality markers associated with a certain value of antioxidant capacity. A broader set of onion genotypes cultivated under different environmental conditions or farming practices has to be analysed to validate individual SSR markers as these factors may have impacts upon analysed traits.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Molecular markers, namely SSR, are widely used in plant breeding as they are associated with certain traits (Collard & Mackill 2008). Presented data confirmed that a previously developed SSR marker set (Mitrová et al 2015) could be used not only for cultivar authentication but also as quality markers associated with a certain value of antioxidant capacity. A broader set of onion genotypes cultivated under different environmental conditions or farming practices has to be analysed to validate individual SSR markers as these factors may have impacts upon analysed traits.…”
Section: Resultssupporting
confidence: 66%
“…A set of 15 microsatellite markers ( Table 2; Jakše et al 2005) were used to establish the DNA profiles of the analysed onion cultivars. PCR was performed as described by Mitrová et al (2015). The amplification products were separated by capillary electrophoresis in an ABI PRISM 3130 sequencer (Applied Biosystems, Foster City, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Other authors reported different allele sizes compared to those described in the original publications. For example, ACM004 gave bands between 201 bp and 212 bp in Czech onion varieties (Mitrová et al 2015); 220 bp and 230 bp in Spanish onion accessions (Mallor et al 2014); and 201 bp and 210 bp in Indian onion accessions (Khar et al 2011). We observed 224 bp and 256 bp bands in Turkish onion accessions using the same marker.…”
Section: Resultsmentioning
confidence: 48%
“…The ACM238 produced the highest number of bands (14). The EST-SSRs markers showed a higher percentage of amplification than in previous reports (Jakše et al 2005;Khar et al 2011;Mallor et al 2014;Mitrová et al 2015). The bands of ACM315 (290 bp), ACM238 (153 bp) and ACM300 (184 bp, 207 bp, 216 bp) were excluded from further evaluation because of being monomorphic across the studied set of 96 accessions.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation